The times they are a-changin': mobile payments in india - Kumar, Deepti; Martin, David; O'Neill, Jacki (ACM - Association for Computing Machinery, 2011)
We report on an ethnographic study of payment and banking practices in India. Currently a mobile payment mechanism is being developed in India and we were interested to see how it would fit with various current payment systems for various types of users. Therefore we studied a variety of current payment situations and gained an understanding of the banking and payment practices and needs of a diverse community. Our aim was to inform the development of interface elements, applications and services that would support the needs we uncovered. We describe our findings and the design ideas they provoked.